In vitro analysis of the effects of plant-derived chondroitin sulfate from intestinal barrier to chondrocytes. (November 2022) - Galla, Rebecca; Ruga, Sara; Ferrari, Sara; Saccone, Sabrina; Saccuman, Laura; Invernizzi, Marco; Uberti, Francesca
Graphical abstract: Highlights: Greendroitine® is a new plant-derived chondroitin sulfate with low molecular weight. Greendroitine® is able to cross the intestinal barrier. Greendroitine® is able to exert beneficial effects on chondrocytes in vitro also in OA condition. Greendroitine® is a promising new nutraceutical candidate to the oral intake in human. Abstract: Chondroitin is well known to regulate several biological functions and to exert a critical role in the regulation of joint physiology maintaining proper chondrocyte activity. The aim of this study was to explore the ability of a new chondroitin, from plant origin, to induce different biological effects analyzing the link between certain chemical properties and the specific biological significance. Its biological effects were analyzed by intestinal permeability and in vitro osteoarthritis conditions verifing data to other chondroitin forms from animal and non-animal sources. Plant-derived chondroitin shows a heterogeneous chemical-biological profile, which may be responsible for many specific functions observed in vitro . Furthermore, it exhibits a better absorption profile without affecting the intestinal barrier and modulates disintegrin and metalloproteinase with thrombospondin 5 motifs to prevent cartilage degradation. Plant-derived chondroitin, Greendroitin®, can be considered an excellent new strategy to improve cartilage trophism, based on surprising biological properties in osteoarthritis in vitro model.